Approximate confidence intervals for moment‐based estimators of the between‐study variance in random effects meta‐analysis. (19th August 2015) - Jackson, Dan; Bowden, Jack; Baker, Rose
Abstract : Moment‐based estimators of the between‐study variance are very popular when performing random effects meta‐analyses. This type of estimation has many advantages including computational and conceptual simplicity. Furthermore, by using these estimators in large samples, valid meta‐analyses can be performed without the assumption that the treatment effects follow a normal distribution. Recently proposed moment‐based confidence intervals for the between‐study variance are exact under the random effects model but are quite elaborate. Here, we present a much simpler method for calculating approximate confidence intervals of this type. This method uses variance‐stabilising transformations as its basis and can be used for a very wide variety of moment‐based estimators in both the random effects meta‐analysis and meta‐regression models. © 2015 The Authors. Research Synthesis Methods published by John Wiley & Sons, Ltd.